Pelatihan Pembuatan Kompos Blok dari Limbah di Desa Sidajaya: Block Compost Training from Waste in Sidajaya Village - Fortuna, Puri Eka Dewi; Safitri, Laras Sirly; Triastuti, Desy; Suroya, Lizza Fauziah; Romalasari, Atika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Block compost is an innovation in the processing of organic waste originating from agricultural land and household waste. The significant potential of organic waste in rural areas presents an opportunity to transform waste into economically valuable products. This activity was carried out in Sidajaya Village, Subang Regency. The objective of this activity was to improve the knowledge and skills of the community in Sidajaya Village. The activity began with the dissemination of information on block compost making, followed by practical sessions on how to create block compost. After this training activity, the community’s knowledge increased by 15.91% compared to before. The community’s skills also improved during the practical session, as demonstrated by the successful production of block compost.